Do global brands contribute to the economy of their country of origin? A dynamic spatial approach. Issue 7 (19th November 2018) - Kucharska, Wioleta; Flisikowski, Karol; Confente, Ilenia
Abstract : Purpose: Brand positioning based on the brand's country of origin is at the centre of attention in international marketing. It is evident that global brands constitute critical intangible assets for businesses and places. However, it is not clear how they contribute to national economies. This paper aims to discuss the significance of brands as contributing to the value of their companies but also helping to leverage national economies. Although global brands can be produced and purchased in multiple countries, their influence on the economy of the country where their owner's seat is located can be more meaningful than in other economies included in the "global factory". Design/methodology/approach: Based on 500 Brandirectory, the Most Valuable Global Brands 2011-2015 rankings powered by Brand Finance, the authors observed a spatial-economic autocorrelation which exemplifies the potential interdependency between gross domestic product (GDP) and brand value. This relationship has become a starting point for designing a spatial regression model. Findings: The findings support the hypothesis that assumptive spatial dependencies have a significant influence on the examined relationship of brand value and GDP. Originality/value: The presented study is the first to examine the potential interdependence between brand values and GDP of the countries of origin using a dynamic spatial approach.